OER@IIUM - Mat Daud, Nuraihan; Abd Hamid, Mohd Azrul Azlen (Centre for Academic Advancement, Universiti Kebangsaan Malaysia & Ministry of Higher Education, 2013)
The International Islamic University Malaysia (IIUM) has Integration, Islamization, Internalization, and Comprehensive Excellence as its missions. In order to achieve these, it is open to innovative ideas which include the adoption of technology in knowledge dissemination. The past few years have seen a steady increase in the number of educational resources that are made accessible to the public. In order to find information on the university, other than on its official website, users also have the option of browsing Wikipedia. Wikipedia is an online free-content website that brings knowledge and resources to everyone who seeks it.